Epidemiologia molecular: polimorfismos genéticos da enzima metilenotetraidrofolato redutase e suas relações com o aborto espontâneo - Cruz, Otávio Martins (2012)
The spontaneous abortion (SA) is characterized as a loss of fetal product before 20 weeks of gestation and its etiology has not completely understood. Numerous studies have shown that polymorphisms in the gene of the enzyme metilenotetrahydrofolate reductase (MTHFR) are involved in susceptibility to AE. Then, the present study was conducted to evaluate the polymorphisms 677C>T and 1298A>C MTHFR gene and their associations in susceptibility to spontaneous abortion in a sample of women in the South of Brazil in a casecontrol approach. Ninety-eight women with SA (cases) and two hundred and twenty-seven healthy women with no history of miscarriage (controls) were studied. Genotyping of MTHFR677C>T and MTHFR1298A>C polymorphisms were analyzed by allele discrimination with TaqMan® pre-designed probes in Real Time PCR. The results showed that there was not difference in the distribution of allelic and genotypes frequencies of MTHFR677C>T and MTHFR1298A>C SNPs between cases and control group. It was observed an increase in the risk of SA in relation to genotype THFR1298CC when compared to genotype MTHFR1298AA (RR: 1,13 95%CI: 1,04; 1,23; p=0.02). Moreover, the classification of the type of abortion is different between genotypes of MTHFR1298A>C polymorphism (p = 0.03). In the control group, non-electron carriers of 677T allele have a higher number of pregnancies than women 677T (p = 0.04). The results presented in our work suggests that the CC genotype of polymorphism MTHF1298A > C is associated with increased risk of SA. However, the polymorphism MTHFR677C>T is not involved in the occurrence of miscarriage in studied population.